Job Equivalency from the Perspective of Organizational Restructuring and Civil Servant Career Development: A Case Study of the Siak Regency Government - Maria Ekowati; Hyronimus Rowa; Melinda Nurcahya Lestari; Rikha Murliasari; Arif Saefudin (Citakonsultindo, 2026)
Bureaucratic simplification has become a strategic agenda in Indonesia’s public sector reform, particularly through the conversion of administrative positions into functional positions. This policy aims to create a more agile, professional, and competency-based bureaucracy while improving organizational effectiveness and public service performance. This study analyzes the implementation of position equalization from structural to functional positions from the perspectives of organizational restructuring and civil servant career development in Siak Regency, Riau Province. A qualitative descriptive approach was employed to explore the dynamics of policy implementation within local government institutions. Data were collected through interviews, observations, and document analysis involving key stakeholders responsible for human resource management and organizational governance. The analysis was guided by organizational design theory and career development theory to examine changes in organizational structure, authority distribution, coordination mechanisms, career planning, competency development, promotion opportunities, and career path certainty. The findings indicate that position equalization has contributed to a leaner organizational structure, improved functional specialization, and greater flexibility in public administration. However, several challenges remain, including competency mismatches, limited understanding of the functional position credit system, and uncertainty regarding long-term career advancement. These issues affect employee motivation and the effectiveness of career management practices. The study proposes an integrative implementation model that aligns organizational restructuring with competency-based career development and merit-based personnel management. Such alignment is essential for strengthening bureaucratic reform and ensuring sustainable professional development within local government institutions.